2016
DOI: 10.1264/jsme2.me15093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Arsenite on the Bacterial Community Structure and Diversity in Soil

Abstract: The impact of arsenite (As[III]) on the bacterial community structure and diversity in soil was determined by incubating soil slurries with 50, 500, and 5,000 μM As(III). As(III) was oxidized to arsenate (As[V]), and the microbial contribution to As(III) oxidation was 70–100%. PCR-denaturing gradient gel electrophoresis revealed that soil bacterial diversity decreased in the presence of As(III). Bacteria closely related to the family Bacillaceae were predominant in slurry spiked with 5,000 μM As(III). The popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Sequences obtained from site I and from site L were related to uncultivated bacteria from different As-contaminated mines or sediments (95–99%, Quéméneur et al, 2008; Heinrich-Salmeron et al, 2011; Yamamura and Amachi, 2014). Finally, clone 55 from site L formed a cluster with the aioA of an uncultivated bacterium (97% to BAP99953) from enrichment cultures with As(III)-spiked paddy soil (Dong et al, 2016) and with the sequence of Nitrobacter hamburgensis X14, a facultative chemolithoautotroph bacterium (Muller et al, 2007). The cluster associated with Betaproteobacteria was related (81–96% identity) to members of the order Burkholderiales .…”
Section: Resultsmentioning
confidence: 99%
“…Sequences obtained from site I and from site L were related to uncultivated bacteria from different As-contaminated mines or sediments (95–99%, Quéméneur et al, 2008; Heinrich-Salmeron et al, 2011; Yamamura and Amachi, 2014). Finally, clone 55 from site L formed a cluster with the aioA of an uncultivated bacterium (97% to BAP99953) from enrichment cultures with As(III)-spiked paddy soil (Dong et al, 2016) and with the sequence of Nitrobacter hamburgensis X14, a facultative chemolithoautotroph bacterium (Muller et al, 2007). The cluster associated with Betaproteobacteria was related (81–96% identity) to members of the order Burkholderiales .…”
Section: Resultsmentioning
confidence: 99%
“…RA-1SW(1), RA-1soil(7), and MA-3(10) were similar to uncultured bacterium aioA gene, clone N-4d5 isolated from sediments in Japan (AB730976, AB731084 and AB838863; (Yamamura et al, 2014). MA-3(7) were closely related to uncultured bacterium aioA gene, clone Aio_aoxBM1-2F/3-2R_L-32 retrieved from soils (LC012221; (Dong et al, 2016). Phylogenetic analysis also showed that arsenite-oxidizing bacteria recovered from samples MA-1soil(2), MA-1soil(17), RA1-1, and MA-1soil(10) were related to uncultured bacterium clone Q6429-2-15 arsenite oxidase (aroA) gene from rhizophere (KP726747, KP726558 and KP726744) ( (Han et al, 2015).…”
Section: Table 44 Summary Of the Number Of Clones And Otus In 12 Samplesmentioning
confidence: 82%